Efek Fraksi Polar Daun Pegagan (Centella Asiatica (L.) Urb) Terhadap Kadar Kolesterol Total Tikus Sindrom Metabolik - Muslim, Muhammad; Budi, Indah Permata (Departemen Kimia FMIPA UNP, 2024)
Metabolic syndrome is a collection of factors including central obsession, dyslipidemia, hypertension, and elevated blood glucose. Centella asiatica leaves (Centella asiatica L.) Urb) which is widely used as a natural medicine, contains antioxidants with the main component containing several secondary metabolites, namely flavonoids, saponins, tannins and terpenoids that can reduce total cholesterol levels. This study aims to determine the effect of the duration of administration of the polar fraction of Centella asiatica leaves (Centella asiatica (L.) Urb) on the reduction of total cholesterol levels in metabolic syndrome rats. The research subjects were 24 male rats which were randomly divided into 6 groups, namely the negative control group which received standard feed and aquadest, while the other 5 groups were induced using high-fat diet for 28 days. Each group was given the preparation, negative group (aquadest), positive control (Na-CMC suspension 0.5%), comparison (simvastatin), treatment group (polar fraction of gotu kola leaf at a dose of 125 mg/kgBW/day, 250 mg/kg BW/day, and 500 mg/kgBW/day) given for 14 days. The measurement of total cholesterol levels was carried out using the CHOD-PAP method. Data were tested using two-way ANOVA. Total cholesterol decreased in all treatment groups after administration of the polar fraction of centella asiatica leaves significantly (p<0.05). The highest decrease was 49.50% in the 500mg/KgBW dose group, followed by the comparison group at 45.58%, followed by the 250mg/KgBW dose at 44.68% and the 125mg/KgBW dose at 41.21%. Based on the results of the study showed that the polar fraction of gotu kola leaves at the time of administration can reduce total cholesterol levels. The effective dose to reduce total cholesterol levels in metabolic syndrome rats was a dose of 500 mg/kgBW